Evaluation method for water-phase expansion performance of ultrahigh-temperature-expansion-resistant graphite blocking agent
By evaluating the thermal expansion performance of expanded graphite in an aqueous environment using optical microscope and image processing software, the limitations of expanded graphite in the prior art in the field of blocking effect evaluation in the drilling fluid field are solved, and more accurate determination of the particle size and mesh of the sealing agent is achieved, and the well wall stability and the use efficiency of drilling fluid are improved.
Patent Information
- Application Number
- CN202510033465.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The prior art is difficult to effectively evaluate the ultra-high temperature expansion performance of expanded graphite in aqueous phase environments, resulting in limitations in its sealing effect and practical application in the field of drilling fluids.
By using an optical microscope to obtain high-definition distribution maps of expanded graphite in the aqueous phase, combined with image processing by Image J software and data analysis by Origin mapping software, the thermal expansion data of expanded graphite in the aqueous phase can be measured and calculated, thereby determining the particle size and mesh number of expanded graphite sealants suitable for specific formations.
This method can more accurately evaluate the aqueous phase expansion performance of expanded graphite, improve the matching degree between the sealing material and formation cracks, reduce the loss of drilling fluid, reduce the risk of well wall instability, and the measurement results are closer to the actual application environment.
Smart Images

Figure CN119880995A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an evaluation method for the water phase expansion performance of an ultra-high temperature expansion resistant graphite plugging agent, and belongs to the technical field of drilling fluid treatment agents. Background Art
[0002] Wellbore stability is a key factor in ensuring the smooth progress of oil and gas exploration and production. It directly affects the safety, production efficiency and economic benefits of oil and gas wells. Wellbore stability problems may lead to wellbore collapse, wellbore diameter reduction, or even complete blockage of the wellbore, thereby increasing operational risks and costs.
[0003] Plugging agents play a vital role in oilfield chemistry, especially in ensuring wellbore stability. They are mainly used to control the loss of drilling fluid and prevent excessive erosion and collapse of wellbore rocks. By effectively blocking rock pores and cracks, plugging agents help maintain the integrity and stability of the wellbore and reduce non-productive time (NPT) during drilling. The selection and use of plugging agents should be based on factors such as rock type, wellbore conditions and drilling fluid properties. High-quality plugging agents can improve the stability of drilling fluids and reduce damage to the wellbore, thereby increasing the production and efficiency of oil and gas wells. In addition, plugging agents can reduce the impact on the environment and avoid potential pollution caused by wellbore instability.
[0004] As a potential plugging agent for drilling fluid, expanded graphite has attracted attention due to its unique physical and chemical properties. It has high compressive strength, good thermal stability and excellent adsorption capacity, which can effectively plug rock pores and cracks and reduce drilling fluid loss. The advantages of expanded graphite in plugging performance are mainly reflected in its layered structure and high expansion, which enables it to form a stable plugging bridge in the drilling fluid, thereby enhancing the stability of the well wall.
[0005] However, the feasibility of expanded graphite as a plugging agent still needs further research and experimental verification. Because it is used in drilling fluid systems, it mainly exerts its plugging effect by expanding in an aqueous environment, and at the same time, it must consider the crack matching relationship caused by the increase in particle size due to thermal expansion in the wellbore before entering the formation. At present, the research on the expansion performance of expanded graphite mainly refers to the National Standard of the People's Republic of China GB / T 10698-1989 "Expandable Graphite". The expansion performance measurement method provided by this standard is measured in a gas phase environment. The measured data has certain limitations on the actual guiding role of expanded graphite in the field of drilling fluids.
[0006] Therefore, providing a method for determining the expansion performance of expanded graphite in an aqueous environment has an important guiding role in the evaluation of the plugging effect of expanded graphite in the field of drilling fluid and its actual field application, so that it can better solve the problem of wellbore instability in ultra-high temperature formations. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention provides an evaluation method for the water phase expansion performance of an ultra-high temperature resistant expanded graphite plugging agent. The method provided by the present invention is closer to the actual application environment of expanded graphite as a drilling fluid plugging agent, and at the same time reduces the influence of the increased cavity volume due to the stacking of expanded particles in the traditional gas phase evaluation method. The data measured based on this method has more practical guiding significance.
[0008] The technical solution of the present invention is as follows:
[0009] A method for evaluating the water phase expansion performance of an ultra-high temperature resistant expanded graphite plugging agent comprises the following steps:
[0010] (1) Weigh k parts of expanded graphite with a mass of m0, place them under an optical microscope for observation and take pictures, and obtain optical pictures P1~P k ; Then put it into deionized water with a volume of V0 and heat it at a temperature of T0 for t0 hours;
[0011] (2) After the hot-rolled expanded graphite is cooled to room temperature, it is stirred evenly, placed under an optical microscope for observation and photographing, and an optical picture P is obtained. k+1 ~P 2k ;
[0012] (3) Use Image J software to process optical images P1~P k and optical images P k+1 ~P 2k , get the measurement data after Image J processing;
[0013] (4) Based on the measured data processed by Image J, the particle size distribution diagram of expanded graphite was drawn using Origin drawing software to obtain the particle size data d0 and d t and standard deviation σ0, σ t ;
[0014] (5) Repeat steps (2) to (4) k times to obtain k particle size data d0, d1, d2, d3, d4, d5, d6, d7, d8, d9, d10, d20, d3, d4, d5, d6, d7, d8, d9, d10 ... t and standard deviation σ0, σ t The average particle size data d0' and d t ' and standard deviation mean σ0', σ t ';
[0015] (6) First, according to the average value of expanded graphite particle size data d0', d t ' and standard deviation mean σ0', σ t', calculate the average expansion ratio r; then according to the average expansion ratio r and the size of the formation fracture to be blocked d m After calculation, the required mesh size of expanded graphite plugging agent is determined based on the size of the formation fractures and the expansion performance of the expanded graphite graphite phase.
[0016] Preferably according to the present invention, in step (1), 80<V0 / m0<120, 25℃<T0<300℃, 0h<t0<16h; the unit of mass m0 is g, the unit of volume V0 is mL, the unit of temperature T0 is ℃, and the unit of time t0 is h.
[0017] Preferably, in step (1), the stirring condition is: stirring at 1800-2200 r / min for 10-20 min.
[0018] According to a preferred embodiment of the present invention, in step (3), the specific method of using Image J software to process the optical image is as follows:
[0019] a. Open Image J software, click File→Open to import optical images P1~P k and optical images P k+1 ~P 2k ;
[0020] b. Select Straight Line in the optical image P1~P k and optical images P k+1 ~P 2k Draw a straight line between the starting point and the end point in the scale;
[0021] c. Click Analyze → Set Scale to open the scale setting window;
[0022] d. Enter the actual length of the line in Known distance and the length unit w in Unit of length.
[0023] e. Click Analyze → Tools → ROI Manger to open the measurement interface, and use the line tool to select at least y sample points. After adding, click Measure to obtain the measurement data processed by Image J in .csv format.
[0024] Preferably, in step (4), the specific method of using Origin drawing software to draw a particle size distribution diagram of expanded graphite is as follows:
[0025] 1) Open the measured data processed by Image J, copy the Length column data into the Origin drawing software, open the drawing tab, select the distribution chart in the statistical chart to draw, and obtain the particle size distribution chart;
[0026] 2) Click the Statistics tab and select Column Statistics in Descriptive Statistics to obtain the particle size data d0 and d t and standard deviation σ0, σ t .
[0027] According to the preferred embodiment of the present invention, in step (5), the average values of the particle size data d0' and d0' of the expanded graphite before and after thermal expansion in the aqueous phase are calculated. t ' and standard deviation mean σ0', σ t The formula for ' is as follows:
[0028]
[0029] Where d0 is the particle size of expanded graphite before thermal expansion in water phase, d t is the particle size of expanded graphite after thermal expansion in water phase, σ0 is the standard deviation of expanded graphite before thermal expansion in water phase, σ t is the standard deviation of expanded graphite after thermal expansion in water phase, and k is the number of expanded graphite.
[0030] Preferably, according to the present invention, in step (6), the formula for calculating the average expansion ratio r is as follows:
[0031]
[0032] Where d0' is the average particle size of expanded graphite before thermal expansion in water phase, d t ' is the average particle size of expanded graphite after thermal expansion in water phase, σ0' is the average standard deviation of expanded graphite before thermal expansion in water phase, σ t ' is the average standard deviation of expanded graphite after thermal expansion in water phase.
[0033] According to a preferred embodiment of the present invention, in step (6), according to the average expansion ratio r and the size d of the formation fracture to be plugged m After calculation, the method to determine the required mesh size of expanded graphite plugging agent under the results of the formation fracture size and the expansion performance of the expanded graphite graphite phase is: according to the 1 / 3 bridging and 2 / 3 bridging rules, in d m / 3 and 2d m / 3 Rigid particles within the particle size range can be used to penetrate the formation fractures m Form an effective plugging; combined with the calculated expansion ratio r, the required expanded graphite plugging agent particle size is obtained as d m / 3r and 2d m / 3r, according to this particle size range, the required mesh size of expanded graphite plugging agent can be obtained.
[0034] The technical features and beneficial effects of the present invention are as follows:
[0035] 1. The present invention provides an evaluation method for the water-phase expansion performance of an ultra-high temperature resistant expanded graphite plugging agent. The method comprises the following steps: firstly, an optical microscope is used to obtain a high-definition distribution map of expanded graphite in a water phase, and then Image J software is used to perform image processing and Origin drawing software is used to perform data analysis, so as to obtain the thermal expansion data of expanded graphite in a water phase. Based on the 1 / 3 bridging rule, the 2 / 3 bridging rule and target layer crack information, an accurate mesh number specification suitable for the formation is given, the matching degree between the plugging material and the formation crack is improved, the drilling fluid loss is reduced, and the risk of wellbore instability during drilling is reduced.
[0036] 2. The evaluation method for the aqueous phase expansion performance of the expanded graphite plugging agent provided by the present invention is mainly obtained by image processing of Image J software, combined with the data analysis function and statistical principles of Origin software to obtain the expansion data of the expanded graphite plugging agent in the aqueous phase. Compared with the traditional method, it has the following advantages: First, the traditional method is to measure the expansion ratio of the sample in the gas phase, which is different from the actual application environment of the expanded graphite plugging agent. The measured data has limited guiding significance for the actual application process, while the evaluation method of the present invention can measure the expansion data of the graphite plugging agent in the aqueous phase, which is closer to its actual use environment; Second, the measurement unit of the traditional method is mL / g. After the expanded graphite plugging agent is thermally expanded in the gas phase, there are a large number of cavities generated by particle accumulation, which makes the measured data much larger than the actual The actual value, while the evaluation method of the present invention collects the particle size data of the expanded graphite plugging agent before and after thermal expansion in the water phase through an optical microscope, processes and analyzes the data based on statistical principles, and the measurement result is closer to the actual value; third, the traditional method test needs to preheat the environment first, and the temperature rises rapidly during the test, while the expanded graphite plugging agent in the actual application environment gradually heats up during the process from the ground to the destination formation in the drilling fluid. In this process, the agent inserted in the graphite sheet will be partially lost due to diffusion, which directly affects the final expansion effect. The method used by the evaluation method of the present invention is closer to the actual construction process, and the measurement result has a stronger guiding significance for actual engineering applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 It is the particle size measurement process of the expanded graphite plugging agent in the water phase before thermal expansion;
[0038] In the figure, (a) Image J is used to import high-definition images, (b) the scale is set, (c) points are selected to measure the particle size, and (d) Orgin is used to draw and process the data.
[0039] Figure 2 It is the process of measuring the particle size of the expanded graphite plugging agent in the water phase after thermal expansion;
[0040] In the figure, (a) Image J is used to import high-definition images, (b) the scale is set, (c) points are selected to measure the particle size, and (d) Orgin is used to draw and process the data.
[0041] Figure 3 The structure diagram of the natural core displacement device for evaluating the plugging effect of expanded graphite plugging agent;
[0042] In the figure, 1. deionized water storage tank, 2. constant flow pump, 3. first intermediate container, 4. second intermediate container, 5. core holder, 6. computer data acquisition system, 7. waste liquid barrel, 8. inlet pressure gauge, 9. confining pressure gauge. DETAILED DESCRIPTION
[0043] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, they will be described in detail with reference to the accompanying drawings and specific embodiments, but are not limited to these. Anything not fully described in the present invention shall be based on conventional techniques in the art.
[0044] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
[0045] The high temperature resistant modified expanded graphite used in the examples was purchased from Qingdao Hengrunda Graphite Co., Ltd.
[0046] Example 1
[0047] A method for evaluating the water phase expansion performance of an ultra-high temperature resistant expanded graphite plugging agent comprises the following steps:
[0048] (1) First, 100 g of expanded graphite with a mesh size of 300 was poured onto kraft paper, stirred evenly with a glass rod, and placed in a culture dish. Five portions of expanded graphite with a mass of 4 g were taken out by the point-taking method, and were respectively placed under an optical microscope for observation and photographing, and high-definition pictures with scale bars were derived to obtain optical pictures P1 to P5; then, the expanded graphite was placed in a volume of 400 mL of deionized water and hot-rolled at a temperature of 200° C. for 2 hours;
[0049] (2) After the hot-rolled expanded graphite is cooled to room temperature, it is stirred at 2000 r / min for 15 min. After the stirring stops, the sample in the middle is sucked with a rubber-tipped dropper, and two drops are dropped on a glass slide. The sample is covered with a cover glass and placed under an optical microscope for observation and photography. A high-definition picture with a scale bar is exported to obtain optical pictures P6 to P 10 ;
[0050] (3) Figures 1-2 As shown, the optical images P1 to P 10 , get the measurement data after Image J processing;
[0051] The specific method of using Image J software to process optical images is as follows:
[0052] a. Open Image J software, click File→Open to import optical images P1~P k and optical images P k+1 ~P 2k ;
[0053] b. Select Straight Line in the optical image P1~P k and optical images P k+1 ~P 2k Draw a straight line between the starting point and the end point in the scale;
[0054] c. Click Analyze → Set Scale to open the scale setting window;
[0055] d. Enter the actual length of the line in Known distance and the length unit w in Unit of length.
[0056] e. Click Analyze → Tools → ROI Manger to open the measurement interface and use the line tool to select at least y sample points. After adding, click Measure to get the measured data processed by Image J in .csv format.
[0057] (4) Based on the measured data processed by Image J, the particle size distribution diagram of expanded graphite was drawn using Origin drawing software to obtain the particle size data d0 and d t and standard deviation σ0, σ t ;
[0058] The specific method of using Origin drawing software to draw a particle size distribution diagram of expanded graphite is as follows:
[0059] 1) Open the measured data processed by Image J, copy the Length column data into the Origin drawing software, open the drawing tab, select the distribution chart in the statistical chart to draw, and obtain the particle size distribution chart;
[0060] 2) Click the Statistics tab and select Column Statistics in Descriptive Statistics to obtain the particle size data d0 and d t and standard deviation σ0, σ t ;
[0061] (5) Repeat steps (2) to (4) for a total of 5 times to obtain 5 particle size data d0, d1, d2, and d3 of the expanded graphite before and after thermal expansion in the aqueous phase. t and standard deviation σ0, σ t The average particle size data d0' and d t ' and standard deviation mean σ0', σ t ';
[0062] Calculate the average particle size data d0' and d0' of expanded graphite before and after thermal expansion in water phase t ' and standard deviation mean σ0', σ t The formula for ' is as follows:
[0063]
[0064] Where d0 is the particle size of expanded graphite before thermal expansion in water phase, d t is the particle size of expanded graphite after thermal expansion in water phase, σ0 is the standard deviation of expanded graphite before thermal expansion in water phase, σ t is the standard deviation of expanded graphite after thermal expansion in water phase, k is the number of expanded graphite;
[0065] The average particle size data d0' of the expanded graphite before thermal expansion in the water phase is 41.10 μm, and the average particle size data after thermal expansion is 327.21 μm, and the corresponding standard deviation average σ0' is 4.3 μm and σ t ' is 8.7μm;
[0066] (6) First, according to the average value of expanded graphite particle size data d0', d t ' and standard deviation mean σ0', σ t ', the average expansion ratio is calculated to be about 6.97 times, and the calculation formula is as follows:
[0067]
[0068] Where d0' is the average particle size of expanded graphite before thermal expansion in water phase, d t' is the average particle size of expanded graphite after thermal expansion in water phase, σ0' is the average standard deviation of expanded graphite before thermal expansion in water phase, σ t ' is the average standard deviation of expanded graphite after thermal expansion in water phase.
[0069] Then, in this embodiment, the natural core with a formation crack size of 900 μm is used. According to the 1 / 3 bridging and 2 / 3 bridging rules, under the result of the formation crack size (900 μm) and the expansion ratio of the expanded graphite phase (6.97 times), the required mesh size of the expanded graphite plugging agent is 300 meshes. The specific calculation method is as follows:
[0070] The particle size of the expanded graphite plugging agent required in this embodiment is d m / 3r and 2d m / 3r, combined with the formation fracture data (900 μm) and the expansion ratio of the expanded graphite phase (6.97 times) in this embodiment, it can be known that the required expanded graphite plugging agent particle size range is approximately between 43 μm and 86 μm, that is, approximately between 200 mesh and 325 mesh. Combined with the existing expanded graphite plugging agent mesh specifications, the required expanded graphite plugging agent mesh is 300 mesh. The relevant data calculation results are shown in Table 1.
[0071] Table 1. Parameters and experimental conditions required to calculate the average expansion ratio of graphite plugging agent in water phase
[0072]
[0073]
[0074] Example 2
[0075] A method for evaluating the water-phase expansion performance of an ultra-high temperature resistant expanded graphite plugging agent. The experimental operation and calculation method refer to Example 1, except that the mesh size of the expanded graphite plugging agent used in the test is 200 meshes.
[0076] According to the test and calculation results, the average particle size data d0' of the expanded graphite before thermal expansion in the water phase is 71.20 μm, and the average particle size data after thermal expansion is 570.70 μm, and the corresponding standard deviation average σ0' is 5.7 μm, σ t ' is 12.3μm, first according to the average value of expanded graphite particle size data d0', d t ' and standard deviation mean σ0', σ t ', the calculated average expansion ratio is about 7.02 times.
[0077] In this embodiment, the natural core of the formation crack to be plugged is 1.5 mm in size. According to the 1 / 3 bridging and 2 / 3 bridging rules, under the formation crack size (1.5 mm) and the result of measuring the expansion ratio of the expanded graphite phase, the required mesh size of the expanded graphite plugging agent is 200 meshes. The specific calculation method is as follows:
[0078] According to the aforementioned inventive method, the required expanded graphite plugging agent particle size is d m / 3r and 2d m / 3r, combined with the formation fracture data and the expansion ratio of the expanded graphite graphite phase in this embodiment, it can be known that the required expanded graphite plugging agent particle size range is approximately between 71.23μm and 142.45μm, that is, approximately between 100 mesh and 200 mesh. Combined with the existing expanded graphite plugging agent mesh specifications, the required expanded graphite plugging agent mesh is 200 mesh. The relevant data calculation results are shown in Table 2.
[0079] Table 2. Parameters and experimental conditions required to calculate the average expansion ratio of graphite plugging agent in water phase
[0080]
[0081]
[0082] Comparative Example 1
[0083] This comparative example takes the expansion test method of 300-mesh expanded graphite in the gas phase as an example, and adopts the traditional method to evaluate the expansion capacity of the graphite plugging agent. The specific steps are as follows:
[0084] (1) First, pour 100g of 300-mesh expanded graphite on kraft paper, stir it evenly with a glass rod, place it in a petri dish, and take out 5 samples of 4g each by the point sampling method;
[0085] (2) Take one of the samples and place it in a quartz beaker that has been burned at 200°C for 5 minutes. Immediately place it in a high-temperature furnace at 200°C. Take it out after 2 hours and read the volume V of the sample after expansion. i (Read the average value of the corresponding scales of the highest and lowest points on the top surface);
[0086] (3) The same operation is performed on the other four samples. The average expansion ratio r0 of the samples is calculated according to formula (6):
[0087]
[0088] The calculation results are shown in Table 3.
[0089] It can be seen from the data in Table 3 that the traditional method can only know the volume after expansion. At the same time, the expansion ratio measured based on this method has limited guiding role in the actual application of graphite plugging agents.
[0090] Table 3. Parameters and experimental conditions required to calculate the average expansion ratio of graphite plugging agent in the gas phase
[0091]
[0092]
[0093] Test example
[0094] This test example uses a natural core displacement experimental device to measure the effect of the expanded graphite plugging agent evaluated in Example 1 on plugging a 900 μm natural core. The structure of the natural core displacement experimental device is as follows: Figure 3 As shown, it includes a deionized water storage tank 1, a constant flow pump 2, a first intermediate container 3, a second intermediate container 4, a core clamp 5 and a waste liquid barrel 7 connected in sequence through pipelines; wherein the first intermediate container 3 and the second intermediate container 4 are connected in parallel, the tops of the two are connected to the side of the core clamp 5, and an inlet pressure gauge 8 and a pipeline valve are arranged on the connected pipeline, and the bottoms of the two are connected to the bottom of the core clamp 5, and a confining pressure gauge 9 and a pipeline valve are arranged on the connected pipeline; the natural core displacement experimental device also has a computer data acquisition system to receive and process information data from the inlet pressure gauge 8 and the confining pressure gauge 9.
[0095] The specific measurement steps are as follows:
[0096] 1) The oven temperature is adjusted to 200°C;
[0097] 2) Load the natural core with an average microcrack size of 900 μm into the core holder 5, connect the pipeline, and apply annular pressure to 10 MPa;
[0098] 3) Fill the first intermediate container 3 with base slurry (prepared with 4% bentonite), close the valve of the plugging agent injection pipeline, open the valve of the base slurry injection pipeline, and saturate the fracture core with base slurry at an injection rate of 9.0 mL / min until continuous base slurry flows out from the outlet;
[0099] 4) Add 400 mL of drilling fluid containing the 300-mesh expanded graphite plugging agent described in Example 1 (prepared with 4% bentonite, and the mass concentration of the 300-mesh expanded graphite plugging agent is 1%) after high-temperature rolling at 200° C. for 2 h into the second intermediate container 4, and keep the stirring rate at 200-300 r / min;
[0100] 5) Close the valve of the base slurry injection pipeline, open the valve of the plugging agent injection pipeline, and inject the plugging agent into the fracture core at an injection rate of 5.0 mL / min until continuous drilling fluid flows out of the outlet. Use a computer data acquisition system to record and process pressure changes in real time. The results are shown in Table 4.
[0101] Table 4. HTHP displacement test results
[0102] Serial number <![CDATA[Average microfracture size of natural core, d m > HTHP flooding test results Example 1 900μm Maximum pressure bearing capacity 6.8MPa Example 2 1.5mm Maximum pressure bearing capacity: 6.4MPa
[0103] It can be seen from the data in Table 4 that when the natural core with an average microcrack of 900 μm is selected for the high temperature and high pressure displacement experiment, it can be seen that the maximum pressure bearing capacity is 6.8 MPa; when the natural core with an average microcrack of 1.5 mm is selected for the high temperature and high pressure displacement experiment, it can be seen that the maximum pressure bearing capacity is 6.4 MPa, indicating that the expansion performance measurement method of the expanded graphite plugging agent evaluated in Example 1 and Example 2 of the present invention in the water phase has certain guiding significance for its actual plugging effect and on-site construction.
[0104] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principles of the present invention, and these improvements and modifications should also be considered as the protection scope of the present invention.
Claims
1. A method for evaluating the water phase expansion performance of an ultra-high temperature resistant expanded graphite plugging agent, characterized in that: The following steps are involved: (1) Weigh k parts of expanded graphite with a mass of m0, place them under an optical microscope for observation and take pictures, and obtain optical pictures P1~P k ; Then put it into deionized water with a volume of V0 and heat it at a temperature of T0 for t0 hours; (2) After the hot-rolled expanded graphite is cooled to room temperature, it is stirred evenly, placed under an optical microscope for observation and photographing, and an optical picture P is obtained. k+1 ~P 2k ; (3) Use Image J software to process optical images P1~P k and optical images P k+1 ~P 2k , get the measurement data after Image J processing; (4) Based on the measured data processed by Image J, the particle size distribution diagram of expanded graphite was drawn using Origin drawing software to obtain the particle size data d0 and d t and standard deviation σ0, σ t ; (5) Repeat steps (2) to (4) k times to obtain k particle size data d0, d1, d2, d3, d4, d5, d6, d7, d8, d9, d10, d20, d3, d4, d5, d6, d7, d8, d9, d10 ... t and standard deviation σ0, σ t The average particle size data d0' and d t ' and standard deviation mean σ0', σ t '; (6) First, according to the average value of expanded graphite particle size data d0', d t ' and standard deviation mean σ0', σ t ', calculate the average expansion ratio r; then according to the average expansion ratio r and the size of the formation fracture to be blocked d m After calculation, the required mesh size of expanded graphite plugging agent is determined based on the size of the formation fractures and the expansion performance of the expanded graphite graphite phase.
2. The evaluation method according to claim 1, wherein: In step (1), 80<V0 / m0<120, 25℃<T0<300℃, 0h<t0<16h; the unit of mass m0 is g, the unit of volume V0 is mL, the unit of temperature T0 is ℃, and the unit of time t0 is h.
3. The evaluation method according to claim 1, wherein: In step (1), the stirring condition is: stirring at 1800-2200 r / min for 10-20 min.
4. The evaluation method according to claim 1, wherein: In step (3), the specific method of using Image J software to process the optical image is as follows: a. Open Image J software, click File→Open to import optical images P1~P k and optical images P k+1 ~P 2k ; b. Select Straight Line in the optical image P1~P k and optical images P k+1 ~P 2k Draw a straight line between the starting point and the end point in the scale; c. Click Analyze → Set Scale to open the scale setting window; d. Enter the actual length of the line in Known distance and the length unit w in Unit of length. e. Click Analyze → Tools → ROI Manger to open the measurement interface, and use the line tool to select at least y sample points. After adding, click Measure to obtain the measurement data processed by Image J in .csv format.
5. The evaluation method according to claim 1, wherein: In step (4), the specific method of using Origin drawing software to draw the particle size distribution diagram of expanded graphite is as follows: 1) Open the measured data processed by Image J, copy the Length column data into the Origin drawing software, open the drawing tab, select the distribution chart in the statistical chart to draw, and obtain the particle size distribution chart; 2) Click the Statistics tab and select Column Statistics in Descriptive Statistics to obtain the particle size data d0 and d t and standard deviation σ0, σ t .
6. The evaluation method according to claim 1, wherein: In step (5), the average values of the particle size data d0' and d t ' and standard deviation mean σ0', σ t The formula for ' is as follows: Where d0 is the particle size of expanded graphite before thermal expansion in water phase, d t is the particle size of expanded graphite after thermal expansion in water phase, σ0 is the standard deviation of expanded graphite before thermal expansion in water phase, σ t is the standard deviation of expanded graphite after thermal expansion in water phase, and k is the number of expanded graphite.
7. The evaluation method according to claim 1, characterized in that: In step (6), the formula for calculating the average expansion ratio r is as follows: Where d0' is the average particle size of expanded graphite before thermal expansion in water phase, d t ' is the average particle size of expanded graphite after thermal expansion in water phase, σ0' is the average standard deviation of expanded graphite before thermal expansion in water phase, σ t ' is the average standard deviation of expanded graphite after thermal expansion in water phase.
8. The evaluation method according to claim 1, wherein: In step (6), according to the average expansion ratio r and the size d of the formation fracture to be plugged m After calculation, the method to determine the required mesh size of expanded graphite plugging agent under the results of the formation fracture size and the expansion performance of the expanded graphite graphite phase is: according to the 1 / 3 bridging and 2 / 3 bridging rules, in d m / 3 and 2d m / 3 Rigid particles within the particle size range can be used to penetrate the formation fractures m Form an effective plugging; combined with the calculated expansion ratio r, the required expanded graphite plugging agent particle size is obtained as d m / 3r and 2d m / 3r, according to this particle size range, the required mesh size of expanded graphite plugging agent can be obtained.
Citation Information
Patent Citations
Nanometer latex micro-crack plugging agent, and preparation method thereof
CN110330955A
High-temperature-resistant intelligent expansion core-shell plugging agent as well as preparation method and application thereof
CN115873567A
High-efficiency plugging agent for drilling fluid and application thereof
CN116042190A
Method for testing thermal expansion performance of petroleum coke
CN117451778A
Nanometer plugging water-based drilling fluid and preparation method and use thereof
US20210163807A1